A cross-sectional study on the determinants of parents' giving vitamin C to their children engaged in sportive activities - Yücel, Ali Serdar; Korkmaz, Murat; Özpinar, Saliha; Öztaş, Dilek; Düz, Serkan; Cihaner, Perihan; Kuyucu, Mihalis (Michael) (Campus Educa Sports Sl, 2026)
The primary objective of this study is to examine the sociodemographic determinants influencing parents' administration of vitamin C to children participating in sports activities. The research was conducted with the participation of 697 parents residing in various districts of Istanbul and having children aged 9-18 years. Data were collected using a questionnaire and analysed using logistic regression, chi-square test, t-test, and multiple regression analyses in the SPSS 25 programme. The child's regular vitamin C use was considered the dependent variable. The parents' educational level, income level, occupational status, and family structure were evaluated as independent variables. When evaluating the findings, we observed that as the level of education increased, parental awareness became more pronounced. In particular, we found that the rate of regular vitamin C use was significantly higher among children of parents with high income levels, university degrees, and office jobs (p<0.05). Another finding was that individuals who exercised regularly were more aware. It was also determined that vitamin C use is more prevalent among children who engage in significantly more weekly exercise and are younger in age (p<0.001). In conclusion, parents' socioeconomic and educational levels play a decisive role in children's immune support behaviours. These findings have the potential to contribute to the development of parent-focused educational programmes and health policies aimed at supporting children's health.
Estudio transversal sobre los factores determinantes de la administración de vitamina C por parte de los padres a sus hijos que realizan actividades deportivas
Keywords: vitamin c use; parental attitudes; sportive children; supplementary foods